2012
DOI: 10.1021/jp207711p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zn-Doped AgInS2 Nanocrystals and Their Fluorescence Properties

Abstract: AgInS 2 nanocrystals have attracted intense attention due to their promising applications in printable solar cells, light-emitting diode (LED), and biological labeling. Although much effort has been made to develop various synthesis methods to prepare AgInS 2 nanocrystals, it remains a goal to obtain high quality AgInS 2 nanocrystals. In this work, Zn-doped AgInS 2 nanocrystals were synthesized by diffusing Zn into the preformed AgInS 2 seeds at high temperature in solution. The resulting Zn-doped AgInS 2 nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
156
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 20 publications
7
156
0
1
Order By: Relevance
“…Development of the methods for synthesis of AgInS 2 nanocrystals (NCs) with a tunable band gap and a high photoluminescence (PL) quantum yield opened new prospects for their application in lightemitting devices [2,3], photovoltaic solar cells [4] and lowtoxic photostable molecular probes [5,6]. Up to date, different strategies have been proposed for synthesis of the AgInS 2 NCs such as: hydrothermal [7], solvothermal [8,9] and hot injection methods [10][11][12][13][14][15], aqueous synthetic route [16] etc. Compared with the organic based approaches, the synthesis in aqueous media is more reproducible, low-cost, environment-friendly, biocompatible, and the as-prepared samples are water soluble, which is especially important for further bio-medical applications [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of the methods for synthesis of AgInS 2 nanocrystals (NCs) with a tunable band gap and a high photoluminescence (PL) quantum yield opened new prospects for their application in lightemitting devices [2,3], photovoltaic solar cells [4] and lowtoxic photostable molecular probes [5,6]. Up to date, different strategies have been proposed for synthesis of the AgInS 2 NCs such as: hydrothermal [7], solvothermal [8,9] and hot injection methods [10][11][12][13][14][15], aqueous synthetic route [16] etc. Compared with the organic based approaches, the synthesis in aqueous media is more reproducible, low-cost, environment-friendly, biocompatible, and the as-prepared samples are water soluble, which is especially important for further bio-medical applications [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that when the [In]:[Ag] molar ratio is 3 or above, a cubic spinel phase of AgIn 5 S 8 is formed [2], and the resulted cation-disordered cubic NCs demonstrate enhanced PL as compared with their tetrahedral or orthorhombic counterparts [2,9]. Incorporation of Zn into AgInS 2 has been shown to be another efficient tool to improve the PL color tunability of the NCs [2,3,10,14,15], while coverage of the AgInS 2 core with a ZnS shell [6,10,13] allows increasing the PL quantum yield up to 80% [10]. The PL of the AgInS 2 NCs irrespective of the method of synthesis is ascribed to the radiative recombination of carriers via intragap levels formed by structural defects [2,12,13,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Ternary AgInS 2 has a distinctive absorption in the visible and near-infrared regions because of its large absorption coefficient and its band gap energy between 1.87 and 2.03 eV, and it is considered one of the potential candidates for promising applications in photovoltaic and photocatalytic fields [16,17]. Various preparation methods for the preparation of AgInS 2 have been reported, such as thermal decomposition [18,19], hot-injection method [20] and hydrothermal method [21]. Coupling of AgInS 2 and TiO 2 NTs would be a perfect strategy to improve the visible light photoelectrochemical property of TiO 2 NTs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a demand to develop alternative semiconductor nanoparticles with low toxicity. I-III-VI ternary semiconductor nanocrystals, such as CuInS 2 and AgInS 2 , have recently attracted much attention [23][24][25][26][27]. They are considered to be the most promising candidates as substitutes for Cd-based quantum dots (QDs) due to their low toxicity.…”
Section: Introductionmentioning
confidence: 99%